2021
DOI: 10.31234/osf.io/9murb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward a Holistic Approach to Reducing Academic Procrastination with Classroom Interventions

Abstract: Academic procrastination is prevalent and a promising target for intervention in educational contexts. Nevertheless, few interventions for procrastination have been rigorously tested. We propose a novel TORCHeS (Theory-driven, Open, Rigorous, Collaborative, Holistic, Small-changes) approach to developing easily implementable and potentially effective classroom interventions for academic procrastination. TORCHeS is motivated by a belief that complex behaviors like academic procrastination require a holistic, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The NCP scale may be helpful in research as well as applied purposes. Self-report scales are often criticized, with behavioral procrastination measures ( Miyake and Kane, 2021 ) or momentary assessment of procrastination in experience sampling ( Wieland et al, 2018 ) suggested as better alternatives. However, the present results indicate an important advantage of self-report measures of procrastination over behavioral measures in that they, in a unique way, address the subjective criteria for problematic and irrational delays as distinct from delays that are unproblematic (e.g., Krause and Freund, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NCP scale may be helpful in research as well as applied purposes. Self-report scales are often criticized, with behavioral procrastination measures ( Miyake and Kane, 2021 ) or momentary assessment of procrastination in experience sampling ( Wieland et al, 2018 ) suggested as better alternatives. However, the present results indicate an important advantage of self-report measures of procrastination over behavioral measures in that they, in a unique way, address the subjective criteria for problematic and irrational delays as distinct from delays that are unproblematic (e.g., Krause and Freund, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, separating procrastinatory behavioral delays from other forms of behavioral delays has proven complicated. In the absence of suitable criteria, researchers have often resorted to behavioral delay in general as a proxy for behavioral procrastination (e.g., Miyake and Kane, 2021 ; Vangsness et al, 2022 ). Even self-report scales measuring procrastination struggle to separate rational delays from suboptimal or irrational delays (e.g., Svartdal and Steel, 2017 ; Svartdal and Nemtcan, 2022 ), resulting in scale scores that include non-procrastinatory delays and thus compromise their validity.…”
Section: Introductionmentioning
confidence: 99%